Greenhouse gas and ammonia emissions from a maize-soybean rotation under no-till as affected by intercropping with forage grass and nitrogen fertilization - Gazola, Bruno [UNESP]; Mariano, Eduardo [UNESP]; Mota Neto, Laudelino V. [UNESP]; Rosolem, Ciro A. [UNESP] (Elsevier, 2024)
Forage grasses intercropped with maize (Zea mays L.) can increase fertilizer N recovery efficiency in agricultural systems. However, their influence on greenhouse gas (GHG) and ammonia (NH3) emissions is still unclear when soybean [Glycine max (L.) Merrill] is grown in rotation. We conducted a two-year (2019–2021) field experiment in Brazil to assess the effect of forage and N fertilization on nitrous oxide (N2O), C dioxide (CO2), methane (CH4), and NH3 emissions in a maize-soybean rotation. Maize was intercropped with ruzigrass (Urochloa ruziziensis cv. Comum), Guinea grass (Megathyrsus maximus cv. Tanzânia) and without forage in the whole plots, as well as fertilized (120 kg N ha−1) or not with N in the split plots. Higher N2O and CO2 fluxes occurred shortly after maize sowing in the first year, with low peaks during the experiment. Methane flux had no notable variation across seasons, even with N addition. Growth of forages did not decrease N2O and CH4 emissions compared with monocropped maize; NH3 far exceeded N2O as an N-loss pathway. Normalized (i.e., yield-scaled) N2O and CH4 emissions were lowest in the second crop year, while ruzigrass and Guinea grass increased such emissions for CO2 and NH3. Despite the well-known benefits of land intensification, intercropping maize with tropical forage grasses is not an effective management practice for mitigating GHG and NH3 relative to maize monocropping. Nonetheless, careful interpretation of the experimental data is advised, given the variable rainfall distribution over the two crop years, which affected gas emissions and crop yields.
Keywords: Intercropping production systems; Megathyrsus; Nitrogen losses; Tropical agriculture; Urochloa; Zea mays L.